2018
DOI: 10.1007/s11883-018-0718-x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Anti-atherosclerotic Effects of PCSK9 Inhibitors From Molecular Biology to Clinical Translation

Abstract: PCSK9 is expressed by various cell types that are involved in atherosclerosis (e.g., endothelial cell, smooth muscle cell, and macrophage) and is detected inside human atherosclerotic plaque. Preclinical studies have shown that inhibition of PCSK9 can attenuate atherogenesis and plaque inflammation. Besides increasing plasma LDL, PCSK9 appears to promote the initiation and progression of atherosclerosis. Inhibition of PCSK9 may confer atheroprotection that extends beyond its lipid-lowering effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 97 publications
0
41
0
1
Order By: Relevance
“…Possible pleiotropic effects of PCSK9 inhibition in atherosclerosis. Reproduced with permission from Nature Springer[148].…”
mentioning
confidence: 99%
“…Possible pleiotropic effects of PCSK9 inhibition in atherosclerosis. Reproduced with permission from Nature Springer[148].…”
mentioning
confidence: 99%
“…This process leads to intimal thickening and the formation of a lipid core that contains lipid-laden foam cells, which is surrounded by a layer of connective tissue [ 33 ]. PCSK9 is a serine protease produced by hepatocytes, endothelial cells, vascular smooth muscle cells, and macrophages [ 34 ] that increases the clearance of LDL-cholesterol receptors by hepatocytes by facilitating the lysosomal degradation of the receptors, which leads to an increase in the serum LDL-cholesterol concentration [ 35 ]. Several studies showed that evolocumab reduced the LDL-cholesterol concentration by 60–70%, decreased triglyceride and lipoprotein (a) concentrations, and increased HDL-cholesterol [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mean LDL-cholesterol concentration at baseline was well controlled by statin therapy (70.4 ± 21.5 mg/dL). It has been suggested that evolocumab has pleiotropic anti-atherosclerotic effects by decreasing oxidative stress, suppressing inflammatory cytokine production, and inhibiting macrophage accumulation [ 34 ]. These findings suggest that evolocumab stabilizes vulnerable coronary plaques and reduces their size by mechanisms independent of its LDL-cholesterol lowering effect in patients whose LDL-cholesterol levels are well controlled with statin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the best-known function of PCSK9 is to target LDLR for lysosomal degradation in hepatocytes, which increases LDL-C and atherosclerotic CVD, PCSK9 may affect atherosclerosis development through its effects on endothelial and vascular smooth muscle cells [21,22]. Moreover, platelet activation and blood clotting factor VIII (FVIII) levels were also shown to be regulated by PCSK9, suggesting that PCSK9 contributes to CVD etiology through regulating many different pathways [23].…”
Section: Structure and Function Of Pcsk9mentioning
confidence: 99%